All Days 2008
DOI: 10.2118/113628-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Rate Control Under Geologic Uncertainty

Abstract: Waterflood optimization via rate control is receiving increased interest because of rapid developments in the smart well completions and i-field technology. The use of inflow control valves (ICV) allows us to optimize the production/injection rates of various segments along the wellbore, thereby maximizing sweep efficiency and delaying water breakthrough. A major challenge for practical field implementation of this technology is dealing with geologic uncertainty. In practice, the reservoir geology is known onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In addition, this step involves the analytical computation of gradients and the Hessian using a streamline-based technique (Alhuthali et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this step involves the analytical computation of gradients and the Hessian using a streamline-based technique (Alhuthali et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is referred to as mean-variance optimization (MVO). Using this approach, Yeten et al (2003), Bailey et al (2005), Alhuthali et al (2008), and Capolei et al (2015b) were able to optimally trade-off expected profit and risk. However, as demonstrated by Capolei et al (2015a), the profit standard deviation may be misleading as a risk measure, when the profit distribution is asymmetrical.…”
Section: Introductionmentioning
confidence: 99%
“…Alhuthali et al (2008) suggested an optimization method based on equalizing arrival time of the waterfront at all production wells for maximizing sweep efficiency. They deal with geologic uncertainty by employing two frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…The first is a stochastic framework that relies on the expected value and variance estimated from multiple realizations. The other approach consists of a min-max formulation that optimizes the worst case scenario (Alhuthali et al, 2008). Applying multiple geological realizations makes an optimization process more challenging.…”
Section: Introductionmentioning
confidence: 99%